Arnold's Projective Plane and 𝑟-Matrices - K. Uchino (Advances in Mathematical Physics)
We will explain Arnold's 2-dimensional (shortly, 2D) projective geometry (Arnold, 2005) by means of lattice theory. It will be shown that the projection of the set of nontrivial triangular 𝑟-matrices is the pencil of tangent lines of a quadratic curve on Arnold's projective plane.